The Training of Reading Beam Notations on Pranada Lines for Children in the Community Reading Park - Syaida Oktira, Yona; Efendi, Nofriza (The Future of Education Journal, 2022)
Block notation is one of the elements in music. Creativity in singing needs to be trained from an early age, with interest and talent, creativity is also very influential with experience. The purpose of this community service implementation is to provide training to read block notation on the rhyme line for children at the community reading park (TBM) in order to children are accustomed to seeing block notation from an early age, students are able to differentiate the tone "do" to tone "re" to tone "mi" and so on, so it is not new thing for students to see the notation of blocks on the sheet music. The implementation method of this community service using the lecture method, demonstration method and practice (data is in qualitative form with descriptive methods) by describing the data in detail and in detail in accordance with the implementation of community service activities. This training explains the shape of block notation, symbols in music, the symbol functions to determine the high and low of the voice, beam notation is divided into 3 parts consisting of flags, stems, and notation heads. Furthermore , it provides training on the value, shape and location of the beat on the line. From this community service activity, the authors got the results, namely: 1) adding knowledge to students in the form of block notation, 2) students being able to read block notation with slash lines and distinguishing the shape and location of tones on the rhyme line, 3) developing interest and students’ talent to appear in front of their friends to sing, 4) students are able to make block notation well, 5) this training produces students who are able to practice solfegio exercises well, 6) this training is participated by elementary school students consists of low class and high class.